Clinical microbiology procedures handbook. Volume 1/ Amy L Leber [editor in chief] - Leber, Amy L
Provides step-by-step protocols and descriptions that enable clinical microbiologists and laboratory staff personnel to perform all analyses, including appropriate quality control recommendations, from the receipt of the specimen through processing, testing, interpretation, presentation of the final report, and subsequent consultation.